Cardiac arrest associated with pregnancy - Mat Nor, Mohd Basri; Mohamed, Abdul Hadi; Othman, Norliza (2011)
The session is based on the latest 2010 AHA guidelines for cardiopulmonary resuscitation in special situation. The frequency of cardiac arrest in pregnancy is on the rise but the survival rates are poor. During attempted resuscitation of a pregnant woman, providers have two potential patients i.e. the mother and the fetus. This session highlights the BLS modifications in this group of patients.